Level of Customer Satisfaction of Selected Online Food Delivery Services at Novaliches Quezon City: Towards Customer Loyalty: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The process of delivering food from restaurants via the Internet is known as online fooddelivery. It is used by applications such as Grab Food and Food Panda or other third-partyfood delivery apps that can see the promos released by the store, and it can be delivered.Online food delivery provides a service that leads to satisfied customers in terms of deliverytime, food quality, promotions, discounts, and so on. The purpose of this research is to find outif the customers are satisfied with the online food delivery services at Novaliches Quezon Cityof the chosen provider by the researcher, who is Grabfood, Foodpanda, and other third-partyfood delivery applications.The results of this study reveal that the total level of customer satisfaction with online fooddelivery evaluated as the majority are “satisfied” in terms of friendly user app, time of delivery,the behavior of delivery, freebies/promos, mode of payment, plenty to choose to menu, anddiscount; but there is one variable that came out in the result “dissatisfied” it is the quality ofproducts, more customers experienced the packaging is not good condition, the product isalready messed up, misassembled product and last wrong item when delivered. The study’sfindings show that one of the most common problems encountered by online food delivery islong delivery time. With the frequency of 66 over 100 respondents, the respondents are mostlywaiting for a long delivery time.The researchers recommended that the mobile application for food delivery must have a clearprocedure, especially for its new users. Furthermore, delivery riders must give moreinformation about the condition of the product and inform the customer about the deliveryperiod to avoid cancellation and complaints. The researchers also recommend practicingvarious interactions, learning better communication, improving problem-solving skills, andtransforming into better people when dealing with customers.
Keywords: Hospitality Management